Do welfare benefit reassessments of people with mental health conditions lead to worse mental health? A prospective cohort study. (March 2020) - Stuart, Ruth; Campbell, Sanchika; Osumili, Beatrice; Robinson, Emily J; Frost-Gaskin, Mary; Pacitti, Richard; McCrone, Paul; Henderson, Claire
Background: There have been cases of suicide following the Work Capability Assessment (WCA), a questionnaire and interview for those claiming benefits due to ill health or disability in the United Kingdom. Aims: To examine whether experiencing problems with welfare benefits, including WCA, among people with pre-existing mental health conditions was associated with poorer mental health and wellbeing and increased health service use and costs. Methods: A prospective cohort study of an exposed group ( n = 42) currently seeking help from a Benefits Advice Service in London and a control group ( n = 45) who had recently received advice from the same service. Questionnaires at baseline and 3-, 6- and 12-month follow-ups. Results: The exposed group had higher mean scores for anxiety ( p = .008) and depression ( p = .016) at baseline and the control group higher mean scores for wellbeing at baseline ( p = .034) and 12 months ( p = .035). However, loss to follow-up makes overall results difficult to interpret. The control group had higher incomes throughout the study, particularly at the 12-month follow-up ( p = .004), but the differences could have been accounted for by other factors. Health service costs were skewed by a few participants who used day-care services intensively or had inpatient stays. Over the study period the proportion of exposed participants engaged in benefits reassessment ranged from 50% to 88%, and 40% to 76% of controls. Conclusion: The hardship of living with financial insecurity and a mental health condition made it difficult for our participants to sustain involvement in a 12-month study and the frequency of benefit reviews meant that the experiences of our controls were similar to our exposed group. These limitations limit interpretation but confirm the relevance of our research. The control data raise the question of whether people with mental health conditions are being disproportionately reassessed.